Analisis Kualitas Pelayanan Dengan Menggunakan Metode Kano (Studi Kasus Pada Wisata Ladaya Kota Tenggarong) - Haryanto Haryanto; Anis Rachma Utary; Musdalifah Azis (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study was to determine the quality and level of satisfaction of visitors to travel Ladaya Tenggarong City, as well as to determine the attributes to be a priority in improving the quality of tourism services Ladaya in order to meet customer satisfaction. Techniques of collecting data by distributing questionnaires. The total sample of 100 respondents using nonprobability sampling techniques. Data analysis technique used is the validity, reliability, suitability level analysis, and methods of analysis servqual canoe. The results showed that the overall quality of services provided by the management Ladaya not said to be satisfactory because of analiss Servqual results indicate that Gap is in a negative position. Based integarsi Servqual and methods Kano showed that of the 21 attributes there are 19 attributes that belong to the priority repairs, while the improvement priority is based on the Evaluation Rule is the main category of Must-Be thereafter One Dimensional, To Category Indifferent is not included in the priority improvements due to the category will not effect the level of visitor satisfaction.Keywords: Service quality; GAP;